Dead famous - Elton, Ben. (London : Black Swan, 2002)
One house, ten contestants, thirty cameras, and forty microphones. Everybody knows the rules#151;total strangers are forced to live together while the rest of the country watches them do it. However, on day 27, one of the housemates isnbsp;killed on live TV.nbsp;Who is the murderer? How did they manage to kill under the constant gaze of the television cameras? Why did they do it? And who will be next?
Keywords: Television serials -- Fiction; Mystery fiction